Physical activity as a mediator of the associations between neighborhood walkability and adiposity in Belgian adults - Van Dyck, Delfien; Cerin, Ester; Cardon, Greet; Deforche, Benedicte; Sallis, James F.; Owen, Neville; de Bourdeaudhuij, Ilse (Health & place, 2010)
This study examined whether physical activity (PA) and sedentary behavior mediated the relationship of neighborhood walkability with two measures of adiposity: body mass index (BMI) and waist-to-height ratio (WHTR). Twenty-four neighborhoods in Ghent, Belgium were selected, stratified by objectively assessed walkability and by socio-economic status. Participants (1200 adults aged 20–65 years) completed the International Physical Activity Questionnaire and wore an accelerometer for 7 days. Weight and height were self-reported and waist circumference was objectively measured. Accelerometer-assessed moderate-to-vigorous PA and self-reported cycling for transport mediated the associations of walkability with BMI and WHTR. Moreover, walking for transport and recreational walking significantly mediated the relationship between walkability and BMI. Sedentary behavior did not mediate associations of walkability with BMI or WHTR. These findings suggest that PA, but not sedentary behavior, is a mechanism by which walkability may affect adults’ adiposity. Planning for neighborhoods to be high in walkability could have favorable effects on physical activity and weight status.